Regulatory adaptive status in determining the effectiveness of treatment with bisoprololum and nebivololum in patients with paroxysmal atrial fibrillation and hypertension - M. A Eremina; V. G Tregubov; V. M Pokrovskiy (КардиоСоматика, 2018)
Increase in mortality from cardiovascular causes, systemic thromboembolism, congestive heart failure, increased frequency of hospitalization and deterioration in quality of life is associated with atrial fibrillation (AF). Essential hypertension (EH) is the most common cause of AF. To prevent recurrence of AF in patients with hypertension b-blockers (b-AB) can be used. Taking into account the possible effect of multidirectional b-AB on the functional condition of the body, in order to determine the effectiveness of therapy, it is advisable to apply a quantitative assessment of the regulatory-adaptive status (RAS). Goal - compare the effectiveness of bisoprololum and nebivololum in patients with paroxysmal AF and EH, given their impact on the RAS. Materials and methods. 50 patients with AF against the background of EH of stages II-III were randomized into two groups for treatment with bisoprololum (5.4±1.8 mg/day, n=25) or nebivololum (5.6±1.6 mg/day, n=25). As part of combination therapy, patients were administered lisinoprilum (14.2±3.8 and 14.3±3.7 mg/day), when required also atorvastatinum (19.1±3.7 and 18.8±4.4 mg/day), acetylsalicylic acid (90.0±4.6 and 91.2±4.1 mg/day), respectively. Initially and in 6 months, the following was done: quantitative assessment of the RAS (cardio-respiratory synchronism test), echocardiography, triplex scanning of brachiocephalic arteries, treadmill test, six-minute walk test, daily monitoring of blood pressure and electrocardiogram, subjective assessment of the quality of life. Results. Both drug regimens comparably suppressed arrhythmia, controlled hypertension, improved the structural and functional condition of the heart. The use of nebivololum positively affected the RAS, to a greater extent increased exercise capacity and improved the quality of life. Conclusion. In patients with paroxysmal AF against the background of EH of stages II-III, the use of nebivololum as part of combination therapy may be preferable to bisoprololum due to its positive impact on the RAS.